Interface passivation using ultrathin polymer–fullerene films for high-efficiency perovskite solar cells with negligible hysteresis. Issue 8 (11th July 2017) - Peng, Jun; Wu, Yiliang; Ye, Wang; Jacobs, Daniel A.; Shen, Heping; Fu, Xiao; Wan, Yimao; Duong, The; Wu, Nandi; Barugkin, Chog; Nguyen, Hieu T.; Zhong, Dingyong; et al.
Abstract : Reducing interface recombination boosts the V oc for perovskite solar cells. Abstract : Interfacial carrier recombination is one of the dominant loss mechanisms in high efficiency perovskite solar cells, and has also been linked to hysteresis and slow transient responses in these cells. Here we demonstrate an ultrathin passivation layer consisting of a PMMA:PCBM mixture that can effectively passivate defects at or near to the perovskite/TiO2 interface, significantly suppressing interfacial recombination. The passivation layer increases the open circuit voltage of mixed-cation perovskite cells by as much as 80 mV, with champion cells achieving V oc ∼ 1.18 V. As a result, we obtain efficient and stable perovskite solar cells with a steady-state PCE of 20.4% and negligible hysteresis over a large range of scan rates. In addition, we show that the passivated cells exhibit very fast current and voltage response times of less than 3 s under cyclic illumination. This new passivation approach addresses one of the key limitations of current perovskite cells, and paves the way to further efficiency gains through interface engineering.